STUDI KELAYAKAN PENGEMBANGAN PARIWISATA KARAHA BODAS KABUPATEN TASIKMALAYA - Yuliawati, Fitriyani; Nurohman, Taufik; Widiastuti, Wiwi; Ramdhani, Hilal (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
The tourism sector is one of the sectors that can drive the Indonesian economy both nationally and locally, thus tourism development can have a positive impact on the development of the community's economy. This study uses a quantitative descriptive research design that collects primary data through the use of surveys. Questionnaires are used in survey research as a technique for collecting basic data. Meanwhile, data on the main points of the study were collected through research using instruments in the form of surveys, interviews, and observations. Based on the results of the study, it can be explained that through the aspects of product, service and management, the Karaha Bodas tourist attraction is worthy of being developed. From the product aspect, based on the results of the interview, it can be seen that the Karaha Bodas tourist attraction is in the development category and the results of the observation show that Karaha Bodas is included in an area with great product support for tourist attractions, based on the parameters that have been set. In terms of service, the results of the study show that Karaha Bodas is included in class II, which supports being used as a tourist destination. In line with that, in terms of management, the results of the study show that it supports being used as a tourist destination. Tourism management in Karaha Bodas needs to be improved to become a sustainable tourist destination based on the Regulation of the Minister of Tourism and Creative Economy/Head of the Tourism and Creative Economy Agency of the Republic of Indonesia Number 9 of 2021 concerning Guidelines for Sustainable Tourism Destinations.